Islands Within Islands: Bacterial Phylogenetic Structure and Consortia in Hawaiian Lava Caves and Fumaroles - Prescott, Rebecca D.; Zamkovaya, Tatyana; Donachie, Stuart P.; Northup, Diana E.; Medley, Joseph J.; Monsalve, Natalia; Saw, Jimmy H.; Decho, Alan W.; Chain, Patrick S. G.; Boston, Penelope J. (Frontiers in Microbiology, 2022)
Lava caves, tubes, and fumaroles in Hawai‘i present a range of volcanic, oligotrophic environments from different lava flows, and host unexpectedly high levels of bacterial diversity. These features provide an opportunity to study the ecological drivers that structure bacterial community diversity and assemblies in volcanic ecosystems, and compare the older, more stable environments of lava tubes, to the more variable and extreme conditions of younger, geothermally active caves and fumaroles. Using 16S rRNA amplicon-based sequencing methods, we investigated the phylogenetic distinctness and diversity, and identified microbial interactions and consortia through co-occurrence networks in 70 samples from lava tubes, geothermal lava caves, and fumaroles on the island of Hawai‘i. Our data illustrate that lava caves and geothermal sites harbor unique microbial communities, with very little overlap between caves or sites. We also found that older lava tubes (500-800 yrs. old) hosted greater phylogenetic diversity (Faith’s PD) than sites that were either geothermally active or younger (less than 400 yrs. old). Geothermally active sites had greater numbers of interactions and complexity than in lava tubes. Average phylogenetic distinctness, a measure of the phylogenetic relatedness of a community, was higher than would be expected if communities were structured at random. This suggests that bacterial communities of Hawaiian volcanic environments are phylogenetically over-dispersed, and that competitive exclusion is a main driver in structuring these communities. This was supported by network analyses that found that taxa (Class level) co-occurred with more distantly related organisms than close relatives, particularly in geothermal sites. Network ‘hubs’ (taxa of potentially higher ecological importance) were not the most abundant taxa in either geothermal sites or lava tubes and were identified as unknown families or genera of the phyla Chloroflexi and Acidobacteria. These results highlight the need for more study of the ecological role of microbes in caves through targeted culturing methods, metagenomics, and long-read sequence technologies.